2006
DOI: 10.2337/db05-0825
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Factor FoxO1 Mediates Glucagon-Like Peptide-1 Effects on Pancreatic β-Cell Mass

Abstract: The glucoincretin hormone glucagon-like peptide-1 (GLP-1) increases pancreatic ␤-cell proliferation and survival through sequential activation of the epidermal growth factor receptor (EGFR), phosphatidylinositol-3 kinase (PI 3-kinase), and Akt. We investigated the role of transcription factor

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
118
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(128 citation statements)
references
References 45 publications
7
118
0
Order By: Relevance
“…GLP-1 is known to activate insulin gene transcription (5), and although we did not directly measure insulin content, there was a trend toward increased insulin immunofluorescence in AdPC1͞3-transduced islet grafts. In addition, it has recently been reported that GLP-1's effects on ␤ cell growth and survival are mediated by means of phosphorylation-dependent nuclear exclusion of FoxO1, which in turn allows increased expression of the transcription factors Pdx1 and Foxa2 (29). Indeed, we did observe greater nuclear Pdx1 staining in the ␤ cells of AdPC1͞3-transduced grafts, suggesting that Pdx1 expression is upregulated in these islets and may contribute to the marked improvement of transplant outcomes.…”
Section: Discussionsupporting
confidence: 56%
“…GLP-1 is known to activate insulin gene transcription (5), and although we did not directly measure insulin content, there was a trend toward increased insulin immunofluorescence in AdPC1͞3-transduced islet grafts. In addition, it has recently been reported that GLP-1's effects on ␤ cell growth and survival are mediated by means of phosphorylation-dependent nuclear exclusion of FoxO1, which in turn allows increased expression of the transcription factors Pdx1 and Foxa2 (29). Indeed, we did observe greater nuclear Pdx1 staining in the ␤ cells of AdPC1͞3-transduced grafts, suggesting that Pdx1 expression is upregulated in these islets and may contribute to the marked improvement of transplant outcomes.…”
Section: Discussionsupporting
confidence: 56%
“…Transduced INS832/13 cells, with a constitutively nuclear FoxO1 mutant, resulted in inhibition of β-cell proliferation induced by GLP-1, suggesting an anti-proliferative role of FoxO1 in pancreatic β cells. Moreover, the effects of GLP-1 were suppressed by an inhibitor of PI-3K (11). In this study, we demonstrated that following exposure to 10 or 100 nM liraglutide for 24 h, the activation of FoxO1 was markedly down-regulated.…”
Section: A B C Dmentioning
confidence: 62%
“…A series of studies have suggested that FoxO1 has a direct effect on pancreatic β-cell differentiation, neogenesis, proliferation and stress resistance (10). A previous study revealed that FoxO1 mediated the proliferative and anti-apoptotic roles of human GLP-1 fragment 7-36 amide in pancreatic β cells (11). Furthermore, studies by Buteau et al demonstrated that GLP-1 increased FoxO1 phosphorylation via activation of phoshatidylinositol-3 kinase (PI-3K)/Akt (also known as protein kinase B, PKB) signaling (11,12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the ␤-cell, insulin or growth factor PI3K/Akt-induced FoxO1 phosphorylation leads to its translocation from the nucleus to cytoplasm, relieving its inhibition of target gene transcription (14). The incretin hormones GIP and glucagon-like peptide 1 (GLP-1) also activate this sequence (19,20). Another is the balance between oxidative stress-induced FoxO1 acetylation and deacetylation (21).…”
Section: Peroxisome Proliferator-activated Receptor ␥ (Ppar␥)mentioning
confidence: 99%